2017
DOI: 10.1038/s41598-017-00623-9
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Lactobacillus gasseri SBT2055 is effective in preventing Porphyromonas gingivalis-accelerated periodontal disease

Abstract: Probiotics have been used to treat gastrointestinal disorders. However, the effect of orally intubated probiotics on oral disease remains unclear. We assessed the potential of oral administration of Lactobacillus gasseri SBT2055 (LG2055) for Porphyromonas gingivalis infection. LG2055 treatment significantly reduced alveolar bone loss, detachment and disorganization of the periodontal ligament, and bacterial colonization by subsequent P. gingivalis challenge. Furthermore, the expression and secretion of TNF-α a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 43 publications
8
83
0
2
Order By: Relevance
“…It is known that IL-1b positively regulates the synthesis of collagenases and prostaglandins and is associated with degradation through proteases, acting directly in the process of inflammation (Bickel et al 2001). Similar results to this study were found when probiotics were used as coadjuvants in the treatment of periodontitis (Messora et al 2016, Ricoldi et al 2017, Kobayashi et al 2017. Similar results to this study were found when probiotics were used as coadjuvants in the treatment of periodontitis (Messora et al 2016, Ricoldi et al 2017, Kobayashi et al 2017.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is known that IL-1b positively regulates the synthesis of collagenases and prostaglandins and is associated with degradation through proteases, acting directly in the process of inflammation (Bickel et al 2001). Similar results to this study were found when probiotics were used as coadjuvants in the treatment of periodontitis (Messora et al 2016, Ricoldi et al 2017, Kobayashi et al 2017. Similar results to this study were found when probiotics were used as coadjuvants in the treatment of periodontitis (Messora et al 2016, Ricoldi et al 2017, Kobayashi et al 2017.…”
Section: Discussionsupporting
confidence: 86%
“…In inflammatory bowel diseases, probiotics offer an alternative or adjunctive approach to conventional therapy (Kerry et al 2018). The main target organ of probiotics is the intestine, but evidence shows that intestinal colonization can cause systemic beneficial effects, promoting protection against diseases at distant sites (Bermudez-Brito et al 2012, Kobayashi et al 2017. The main target organ of probiotics is the intestine, but evidence shows that intestinal colonization can cause systemic beneficial effects, promoting protection against diseases at distant sites (Bermudez-Brito et al 2012, Kobayashi et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid bacteria have been used in many fermented foods around the world and are well adapted to human life. Several strains of lactic acid bacteria have been reported to induce the expression of antimicrobial peptides . In addition, we have revealed that the upregulation of β‐defensin by L. helveticus is higher than other Lactobacillus species in vitro (unpublished data).…”
Section: Introductionmentioning
confidence: 72%
“…The design of animal experiment was based on our previous report . Eight‐week‐old female BALB/c mice were divided into three groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation